mRNA Expression of EgCHI1, EgCHI2, and EgCHI3 in Oil Palm Leaves (Elaeis guineesis Jacq.) after Treatment with Ganoderma boninense Pat. and Trichoderma harzianum Rifai - Laila Naher; Soon Guan Tan; Chai Ling Ho; Umi Kalsom Yusuf; Siti Hazar Ahmad; Faridah Abdullah (The Scientific World Journal, 2012)
Background. Basal stem rot (BSR) disease caused by the fungus Ganoderma boninense is the most serious disease affecting the oil palm; this is because the disease escapes the early disease detection. The biocontrol agent Trichoderma harzianum can protect the disease only at the early stage of the disease. In the present study, the expression levels of three oil palm (Elaeis guineensis Jacq.) chitinases encoding EgCHI1, EgCHI2, and EgCHI3 at 2, 5, and 8 weeks inoculation were measured in oil palm leaves from plants treated with G. boninense or T. harzianum alone or both. Methods. The five-month-old oil palm seedlings were treated with Gano-wood blocks inoculum and trichomulch. Expression of EgCHI1, EgCHI2, and EgCHI3 in treated leaves tissue was determined by real-time PCR. Results. Oil palm chitinases were not strongly expressed in oil palm leaves of plants treated with G. boninense alone compared to other treatments. Throughout the 8-week experiment, expression of EgCHI1 increased more than 3-fold in leaves of plants treated with T. harzianum and G. boninense when compared to those of control and other treated plants. Conclusion. The data illustrated that chitinase cDNA expression varied depending on tissue and the type of treatment.